2003
DOI: 10.1016/s0169-2070(02)00011-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of forecasting methods for hotel revenue management

Abstract: The arrivals forecast is one of the key inputs for a successful hotel revenue management system, but no research on the best forecasting method has been conducted. In this research, we used data from Choice Hotels and Marriott Hotels to test a variety of forecasting methods and to determine the most accurate method. Preliminary results using the Choice Hotel data show that pickup methods and regression produced the lowest error, while the booking curve and combination forecasts produced fairly inaccurate resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
183
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 13 publications
2
183
0
2
Order By: Relevance
“…Time series analysis is also used in tourism sector. Weatherford and Kimes [13] applied different forecasting methods on hotel revenue management and recommended that exponential smoothing, pickup, and moving average models were the most suitable for forecasting as well as revenue generation.…”
Section: Journal Of Industrial Engineeringmentioning
confidence: 99%
“…Time series analysis is also used in tourism sector. Weatherford and Kimes [13] applied different forecasting methods on hotel revenue management and recommended that exponential smoothing, pickup, and moving average models were the most suitable for forecasting as well as revenue generation.…”
Section: Journal Of Industrial Engineeringmentioning
confidence: 99%
“…Combined models use either regression or a weighted average of historical data and advanced booking models to develop forecasts. A review of forecasting methods for all three types is found in Weatherford andKimes, 2008 andFrechtling, 2001. In this study particular interest is devoted to reservation data as it is very rich and contains very useful information indicating the actual demand to come.…”
Section: Related Work and Problems Adressedmentioning
confidence: 99%
“…Successful application of revenue management requires hotels being able to forecast demand. Th erefore, a high proportion of the research literature is dedicated to forecasting from theoretical and methodological perspective (Burger, Dohnal, Kathrada & Law, 2001;Frechtling, 2001;Tranter et al, 2008; Weatherford, Kimes & Scott, 2001;Weatherford & Kimes, 2003, among others), summarized in Table 4.…”
Section: Forecastingmentioning
confidence: 99%